The Canon Pro and Contra: ’The Canon is Dead-Long Live Pick and Mix’ - Grabes, Herbert (Miscelánea: A Journal of English and American Studies, 2004)
The chief argument against the traditional canon is, of course, that it has been a vehicle for national superiority. Yet it is indubitably the case that the creation of a canon of English literature over the centuries is indeed closely bound up with the formation of British national identity. What was produced in this way was largely “an entirely gentlemanly artefact” (to use Lillian S. Robinson’s phrase for the blatant neglect of women authors), as has been amply demonstrated by feminist scholars in recent decades. Quite apart from this, however, the traditional British versions of the canon of English literature are astonishingly broad and are much less in need of an “opening up” than many of the more belligerent “canon busters” claim. Without denying that any canon-making implies competition and value-statements that create hierarchies, it is argued that the formation of literary canons is indispensable in order to keep the literature of the past within cultural and collective memory (not forgetting, too, that the past begins yesterday). Only those acquainted with a fair amount of our literary heritage, after all, will have a chance to individually “pick-and-mix” —and thus to subvert the canonical order that has been their starting-point. This also means that the canon is not a sanctuary but an ongoing project— and one that we relinquish at our collective peril.